Bemerkungen zur ökonomischen Analyse von Sicherheit - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
This paper is a comment on the analysis of the German security industry by Stuchtey and Skrzypietz (2014). The comment focuses on two issues. Firstly, it argues that it is advantageous for the research agenda of the authors to conceptualize security as a human need and not as an economic good. The need for security, then, can be viewed to get satisfied by various goods (products and services including, inter alia, personal security and bodyguarding, security services, alarm and video surveillance equipment or antivirus software) that are partly offered by the German government and partly by private companies on competitive markets. Secondly, it suggests a slightly different theoretical framework in order to streamline both the conceptual thinking and the empirical analysis of the paper, in particular with a view to the issue of a postulated trend towards the privatization of security goods.
Keywords: L80; H40; B52; 330; economics of security; German security industry; privatization; goods classification